2020
DOI: 10.3390/biomedicines8090338
|View full text |Cite
|
Sign up to set email alerts
|

Potent Small-Molecule Inhibitors Targeting Acetylated Microtubules as Anticancer Agents Against Triple-Negative Breast Cancer

Abstract: Microtubules are one of the major targets for anticancer drugs because of their role in cell proliferation and migration. However, as anticancer drugs targeting microtubules have side effects, including the death of normal cells, it is necessary to develop anticancer agents that can target microtubules by specifically acting on cancer cells only. In this study, we identified chemicals that can act as anticancer agents by specifically binding to acetylated microtubules, which are predominant in triple-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…[10] Thus, these limitations compelled us to search for novel anticancer agents with high potency, less toxicity in normal cells, and an exclusive target of the action. [11,12] Herein, we report the synthesis and biological evaluation of 1,2,3-triazoles with different azide derivatives as potential anticancer agents. [13] Azoles are one of the important classes of five-membered nitrogen-containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Thus, these limitations compelled us to search for novel anticancer agents with high potency, less toxicity in normal cells, and an exclusive target of the action. [11,12] Herein, we report the synthesis and biological evaluation of 1,2,3-triazoles with different azide derivatives as potential anticancer agents. [13] Azoles are one of the important classes of five-membered nitrogen-containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we demonstrated that the overall survival rate was severely reduced in breast cancer patients in whom the expression levels of ATAT1 and the five aforementioned genes were negatively correlated. Therefore, analysis of the expression levels of these genes will be useful for the diagnosis of triple-negative malignant breast tumors in future, and inhibition of microtubule acetylation might be a useful strategy for triple-negative breast cancer treatment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there are pharmacological agents that promote increased MT acetylation through inhibition of deacetylases, currently there are no available pharmacological inhibitors of α -TAT1 itself, although there appears to be a considerable interest in the development of such inhibitors 74 . Identifying a small chemical targeted to the C-terminus signal motif to alter the subcellular localization, instead of the catalytic activity, may open up a novel approach for inhibiting MT acetylation.…”
Section: Cytoplasmic Localization Ofmentioning
confidence: 99%